Loving Your Parents and Treating Others Well: The Effect of Filial Piety on Cyberbullying Perpetration and Its Functional Mechanism Among Chinese Graduate Students - Wei, Hua (Journal of interpersonal violence, 2022)
Although a few studies have investigated the effect of family factors on cyberbullying perpetration, these studies have mainly focused on the roles of parents. Few studies have examined the roles of children. In traditional Chinese culture, the filial piety belief (FPB) refers to the viewpoint that considers the roles of children in a family context. We suggest that how children consider their roles in a family might also influence cyberbullying perpetration. Based on the dual filial piety model and social information processing model, this study examined the effect of FPB on cyberbullying perpetration and tested its mediation of hostile attribution bias. In total, 588 graduate students participated. The participants completed several questionnaires, including the FPB scale, the social information processing?attribution response questionnaire, and the cyberbullying scale. The results were as follows. First, reciprocal filial piety (RFP) was significantly negatively correlated with hostile attribution bias and cyberbullying perpetration, while authoritarian filial piety (AFP) was significantly positively correlated with hostile attribution bias and cyberbullying perpetration. Second, hostile attribution bias mediated the association between FPB (comprising AFP and RFP) and cyberbullying perpetration; RFP decreased hostile attribution bias, while AFP increased hostile attribution bias; and hostile attribution bias increased cyberbullying perpetration. The current study expands our understanding of the influential factors and formation mechanism of cyberbullying perpetration in Chinese culture.